A Mathematical Model on the Immune System Role in Achieving Better Outcomes of Cancer Chemotherapy - Gil, W.f.f.m.; Carvalho, T.; Mancera, P.f.a.; Rodrigues, D.s. (Sociedade Brasileira de Matemática Aplicada e Computacional, 2019)
ABSTRACT The incidence of neoplastic diseases shows that the search for more effective cancer treatments is still necessary. In addition to standard treatments such as chemo- and radiotherapy, new treatment modalities have been focused in recent advances in immunology. Since little has been discussed about the biological implications of chemotherapy with respect to its impact on the immune system and on the other normal, “healthy” cells, we devote the present mathematical modeling work to do so. First, we prove the invariance of the region where all state variables remain positive (i.e., the number of cancer cells, normal cells and immune cells, and also the amount of chemotherapy). Afterward, we analyze the model in terms of the linear stability of the system and establish a necessary and sufficient condition for the local stability of the cure equilibrium point. Moreover, we simulate some scenarios involving both the immune system and chemotherapy, showing that a reasonable treatment strategy occurs when these are combined suitably.

RESUMO A incidência de doenças neoplásicas mostra que a busca por tratamentos mais eficazes contra o câncer ainda é necessária. Além dos tratamentos padrão, como quimioterapia e radioterapia, novas modalidades de tratamento têm sido focadas nos recentes avanços na imunologia. Como pouco tem sido discutido sobre as implicações biológicas da quimioterapia em relação ao seu impacto tanto no sistema imunológico como em outras células normais e “saudáveis”, dedicamos o presente trabalho de modelagem matemática a fazê-lo. Primeiro, provamos a invariância da região na qual todas as variáveis de estado permanecem positivas (ou seja, o número de células cancerosas, células normais e células imunes, e também a quantidade de quimioterapia). Em seguida, analisamos o modelo em termos de estabilidade linear do sistema e estabelecemos uma condição necessária e suficiente para a estabilidade local do ponto de equilíbrio de cura. Além disso, simulamos alguns cenários envolvendo tanto o sistema imunológico quanto a quimioterapia, mostrando que uma estratégia de tratamento razoável ocorre quando estes são combinados adequadamente.
Keywords: cancer; immune system; chemotherapy; mathematical modeling; ordinary differential equations; câncer; sistema imune; quimioterapia; modelagem matemática; equações diferenciais ordinárias